Angiotensin converting enzyme inhibitors in acute myocardial infarction - Opolski, Grzegorz; J. Filipiak, Krzysztof; Grabowski, Marcin (Przewodnik Lekarza/Guide for GPs, 2005)
Most randomized, placebo -controlled trials have demonstrated that angiotensin converting enzyme (ACE) inhibitors started early in acute myocardial infarction improves left ventricular function and prognosis after myocardial infarction. This article summaries current knowledge and recommendation for use ACE inhibitors acute myocardial infarction.